2019
DOI: 10.5492/wjccm.v8.i5.74
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of acute pulmonary inflammation in critically ill patients: The role of inflammatory biomarkers

Abstract: Pneumonia and acute respiratory distress syndrome are common and important causes of respiratory failure in the intensive care unit with a significant impact on morbidity, mortality and health care utilization despite early antimicrobial therapy and lung protective mechanical ventilation. Both clinical entities are characterized by acute pulmonary inflammation in response to direct or indirect lung injury. Adjunct anti-inflammatory treatment with corticosteroids is increasingly used, although the evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 88 publications
1
50
0
Order By: Relevance
“…CRP levels can be used for early diagnosis of pneumonia [3], and patients with severe pneumonia had high CRP levels. It is an important index for the diagnosis and assessment of severe pulmonary infectious diseases [17]. Matsumoto's study also showed the value of CRP levels in severe pneumonia [18].…”
Section: Discussionmentioning
confidence: 96%
“…CRP levels can be used for early diagnosis of pneumonia [3], and patients with severe pneumonia had high CRP levels. It is an important index for the diagnosis and assessment of severe pulmonary infectious diseases [17]. Matsumoto's study also showed the value of CRP levels in severe pneumonia [18].…”
Section: Discussionmentioning
confidence: 96%
“…[ 15 , 16 ] Some studies have shown that, the CRP and PCT of patients with new crown and diabetes mellitus were significantly higher than those of patients without diabetes mellitus, and the immune system was greatly inhibited. [ 17 19 ] Thus, the novel coronavirus can affect the clinical cure rate of diabetic foot patients, delay the healing time, increase the amputation rate and mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…PCT is a 116 amino acid protein encoded by the CALC-1 gene, which typically exists in low concentrations in parafollicular cells of the thyroid gland in healthy individuals. In the presence of an infection, CALC-1 gene expression is induced in non-neuroendocrine cells, resulting in increased PCT levels [23]. As a clinical biomarker of bacterial infections, PCT levels are measured to assess the severity and prognosis of CAP, acute respiratory distress syndrome, and sepsis, and guide antibiotic and glucocorticoid treatment [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of an infection, CALC-1 gene expression is induced in non-neuroendocrine cells, resulting in increased PCT levels [23]. As a clinical biomarker of bacterial infections, PCT levels are measured to assess the severity and prognosis of CAP, acute respiratory distress syndrome, and sepsis, and guide antibiotic and glucocorticoid treatment [23][24][25][26][27]. While several studies have investigated the relationship between PCT and Streptococcus pneumoniae, Haemophilus influenzae, and other common bacterial pathogens in patients with CAP, few clinical studies have assessed this relationship in patients with MPP [28].…”
Section: Discussionmentioning
confidence: 99%